Deconstructing Gangsterism in the Western Cape Policy Response to the National Anti-Gangsterism Strategy - Viltoft, Clara Dybbroe (2021)
In the Province of the Western Cape in South Africa, gangsterism continues to be associated with issues of violence, crime and localised conflicts, affecting residents on the Cape Flats in particular. Although the country's legal framework promotes human rights and despite ongoing interventions by law enforcement, the effectiveness of government responses is still debated by politicians as well as the general public. Using Carol Bacchi's ‘What's the Problem Represented to Be' (2009) approach to policy analysis, the aim of this dissertation is to deconstruct the Western Cape's political problematisation and representation of the ‘problem' by analysing the Western Cape Provincial Policy response to the National Anti-Gangsterism Strategy. From a social constructivist angle, this dissertation presumes policy as prescriptive guidelines that dictate action. Further, the aim is to discover how the problem is understood and represented and thus analyse which discourses and material responses are generated and which are not. The findings confirm that there is a discrepancy between what is articulated in policy and what actually happens on the ground, i.e. between discourse and practice. Moreover, it will be argued that sustained anti-gang intervention demand that structural obstacles and inequality in lieu of the spill over from the Apartheid era are addressed. Taking notice of these aspects, the minor dissertation concludes that it is critical to figure out how best to transform conflict conditions in areas with high levels of gang violence with the view to allowing both youth groups and individuals to exert agency and become empowered in pursuit of individual and community resilience